Developments in Narrow Beam Echo Sounders - MacPhee, S. B. (The International Hydrographic Review, 2015)
To accurately delineate the sea floor in areas of irregular sea bottom topography, it is necessary that a narrow beam sounding system be employed and that the transducer be stabilized in pitch and roll. In early 1973 an investigation was commenced on the types and availability of various narrow beam echo sounders for hydrographic and oceanographic use. This search concluded with the selection of a narrow beam echo sounder for initial fitting on CSS Hudson. In this paper the various types of narrow beam echo sounders available, along with their limitations and capabilities in hydrographic and oceanographic surveys, are discussed.